The Strategic Role of Religious Authority in Supporting State Policy on Non-Natural Disaster Management in Indonesia - Mahsun, Muhammad; Khoir, Tholkhatul; Mufrikhah, Solkhah; Masrohatun; Hashim, Shahrin (Jurnal Theologia, 2025)
The COVID-19 pandemic has not only posed a grave threat to global public health but also disrupted the socio-religious fabric of Indonesian society, particularly in how Muslims perform communal worship. In response to government-mandated restrictions, resistance emerged from various societal groups, exposing a growing distrust toward state policy and weakening public compliance. This study investigates the strategic role of the Indonesian Ulema Council (MUI) as a religious authority in supporting government efforts to manage COVID-19 as a non-natural disaster. Specifically, it addresses two key questions: (1) How did MUI contribute to the government's pandemic response through its fatwas? and (2) What was the strategic significance of these fatwas in the broader context of state development? Employing a qualitative case study approach, data were gathered through field observation, interviews, and document analysis in three regions of Central Java. The findings reveal that MUI fatwas were instrumental in aligning religious practice with public health directives at macro, meso, and micro levels. Through its fatwas and outreach programs, MUI functioned as both a moral guide and policy communicator. This study contributes to the discourse on religion-state relations in new democracies and highlights how religious legitimacy can enhance state resilience during public crises.